Design of a New Semiconductor Circuit Breaker - Hassan, Mohd Zin (2008)
The objective of this present work is to design, simulate and testing the new semiconductor circuit breaker. In this thesis, both circuit breakers are built around electronics and semiconductor devices. The designed circuit applies solid state technology to provide relay control and op to coupler device as interface between electronics control circuit and power supply side. The design combines solid-state switching, analog signal output to perform circuit protection and earth leakage circuit breaker. The simulation has been carried out using the OrCAD simulation software. The real performance of the designed semiconductor circuit breaker has been measured using oscilloscope. The analysis has been carried out on the single phase and three phase loads. The tripping time has been measured during the short circuit test. Waveforms of the simulations showed that the tripping time is 2 ms on the single phase load and 2 ms on the three phase load. The short circuit test has been carried out showed the tripping is 2 ms on the single phase load and 2 ms on the three phase load. Comparison of the tripping time has been made between the designed semiconductor circuit breaker and conventional circuit breaker which is available on the market. Data sheet of the conventional circuit breaker showed the tripping time is more than 20 ms. Its means that the performance of the tripping time of the semiconductor circuit breaker is much better than the conventional electromechanical circuit breaker.